Traumas, sedução, sonhos e fantasia: o arcaico e a disposição à neurose em Sigmund Freud - Fritz, Vinícius Fratta (2022)
In the text “A fantasia freudiana”, Luiz Roberto Monzani leads us through an investigation in which the place of the controversial 'fantasy'/phylogenetic hypothesis - contained in the text found by Ilse Grubrich-Simitis in the 1950s, entitled "Übersicht der Übertragungsneurosen", or “Transference neurosis: a synthesis” - is demonstrated through the examination of some specific texts from the work of Sigmund Freud. If one takes the commentator's statement that from his first writings to the end of his work, Freud maintains a certain etiological equation whose essence remains more or less the same, without denying the influence of external and internal factors, it seems crucial to consider the writings of 1890 to 1900, in order to reconstruct the nuances of the psychoanalyst's thought in order to assess how this hypothesis is directly related to Freud's initial scientific work, since it objectively attempts to respond to theoretical problems involved in the very creation of psychoanalysis, in the specific context of transition from the seduction theory to the fantasy theory, which took place in the last decade of the 19th century. The present study is a demonstration of the way in which the circumscription of psychoanalysis around its own objects also creates the theoretical condition for the phylogenetic hypothesis to be conceived later.